(untitled) - Cowan, M. Kelly (Boston, 2006)
Up-to-date and extensively reviewed, "Microbiology" is written with the non-major/allied health student in mind. Offering both an engaging writing style through the use of case studies and analogies and a vivid art program, the text thoroughly explains difficult microbiology concepts in an accessible manner. Utilizing an organ systems approach, the unique in-chapter organization of the disease/clinical chapters provides students a realistic viewpoint of the clinical experiences they will encounter in the future
Keywords: Microbiology